Buying under Influence: Interaksi Antara FOMO, Teman Sebaya dan Pengendalian Diri Terhadap Perilaku Belanja Impulsif di Kalangan Generasi Z - Maulana Fajar Hanafi (Universitas Muria Kudus, 2026)
This study aims to analyze the influence of influencers, peer influence, FoMO, and self-control on impulsive buying, while also examining the role of FoMO as a mediator and the effect of self-control as a moderator of FoMO. This study used a non-probability purposive sampling method where respondents were Gen Z students at various universities in Central Java who actively made purchases through e-commerce in the last 2 months (May to July 2025). From the results of the research observations conducted, there were 161 selected respondents with an average purchase frequency of 25 times on e-commerce. After checking the answers of each respondent, it was found that 27 questionnaires were incompletely answered on several items related to variables, resulting in 134 valid questionnaires for further analysis. Data analysis used the partial least squares method. The results showed that influencers, peer influence, and FoMO as mediators were able to have a significant impact on impulsive buying behavior. Furthermore, this study also explained that self-control can reduce the influence of FoMO, weaken the influence of FoMO on impulsive buying, and reduce the tendency of impulsive buying by consumers among Gen Z.